When Hitler Stole Pink Rabbit - Kerr, Judith (New York : Putnam & Grosset Group, 1997)
Recounts the adventures of a nine-year-old Jewish girl and her family in the early 1930's as they travel from Germany to England.
"Ages 8-12"--P. [4] of cover.
Keywords: Jews -- Germany -- History -- 1933-1945 -- Fiction; Family life -- Fiction